Ultrasound markers of adolescent polycystic ovary syndrome according to a complex three-dimensional transrectal ultrasound - Yu P Grigorenko; E V Uvarova; V L Ogryzkova; L A Ashrafyan (IP Berlin A.V., 2015)
The results of a complex three-dimensional transrectal ultrasound of internal genitals of 83 virgins aged from 14 to 16 years with clinical and the hormonal confirmed polycystic ovary syndrome (PCOS) are hereby discussed. The control group consisted of 20 healthy contemporaries having regular menstruations and normal values of hormones. As a result of complex inspection it was established that in an adolescent with PCOS the volume of ovaries is 3 times higher , than in control group; also, there were 3 times more varicosities of internal vessels of pelvis minor, and 2,1 times more often - a hypervascularization of a stroma of ovaries occurred. Taking into account the sizes and an arrangement of follicles at PCOS we have allocated an equal type (57%) and mixed type (43%) of ovarian structure, contributing to the difference in hormonal status and organ sizes.